2023
DOI: 10.3390/cancers15153827
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mesenchymal Epithelial Transition Factor (MET) and Its Impact in the Development and Treatment of Non-Small-Cell Lung Cancer

Embla Bodén,
Fanny Sveréus,
Franziska Olm
et al.

Abstract: Lung cancer represents the leading cause of annual cancer-related deaths worldwide, accounting for 12.9%. The available treatment options for patients who experience disease progression remain limited. Targeted therapeutic approaches are promising but further understanding of the role of genetic alterations in tumorigenesis is imperative. The MET gene has garnered great interest in this regard. The aim of this systematic review was to analyze the findings from multiple studies to provide a comprehensive and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“… 45 Under pathologic conditions, mutations in the MET gene can cause aberrant activation of exon 14. 46 Such sustained tyrosine kinase activity fosters tumor cell migration, proliferation, and infiltration. 47 Studies suggest that MET mutations are found in 3% to 5% of patients with NSCLC, with MET amplification observed in 1% to 5%.…”
Section: Pathogenesis Of Nsclcmentioning
confidence: 99%
“… 45 Under pathologic conditions, mutations in the MET gene can cause aberrant activation of exon 14. 46 Such sustained tyrosine kinase activity fosters tumor cell migration, proliferation, and infiltration. 47 Studies suggest that MET mutations are found in 3% to 5% of patients with NSCLC, with MET amplification observed in 1% to 5%.…”
Section: Pathogenesis Of Nsclcmentioning
confidence: 99%